05 Exploring why 'primary care' problems end up receiving ambulance treatment: early findings from a pre-hospital ethnographic study. Issue 10 (28th September 2017) - Brooker, Mathew; Barnes, Rebecca; Heawood, Alison; Purdy, Sarah
Abstract : Background: An increasing part of the Ambulance Service workload can more accurately be described as 'urgent care' cases, many of which could potentially be managed by timely contact with Primary Care. Previous work by this team and others has sought to define what constitutes a 'primary care sensitive' contact with Ambulance Services. The complex reasons driving the increase in such contacts remain unclear. Methods: This study is utilising complementary qualitative methods to explore exemplar 'primary care sensitive' cases, identified by a GP accompanying front-line ambulance crews to calls across a range of shifts in a typical NHS Ambulance Trust. The study is on track to complete 160 hours of observation and recruit 50 cases. Detailed ethnographic field notes and reflexive diaries supplement semi-structured interviews with patients, carers and 'in-the-moment' purposful conversations with ambulance staff. Analysis of call recordings associated with each case, Document Analysis of Primary Care records and interviews with patients' GPs provide additional triangulation. Results: Data collection and analysis are ongoing, but initial findings indicate that the process of seeking help on behalf of someone else can change the way uncertainty is handled and projected. There appears to be an emerging typology of 'triggers' that prompt contact with ambulance services for Primary Care problems. Some aspects of ambulance care are highly valued by patients and carers. These valued aspects may offset the practical limitations that the ambulance service faces in fully resolving the clinial situation. Both ambulance clinicians and Primary Care clinicians use similar strategies to manage expectations. Conclusions: We discuss possible implications for both Primary Care and Ambulance providers in the ways patients and their carers can be supported to access services. As urgent care is increasingly being delivered in a range of settings, patients may be viewing their 'route in' to acute services as less important than the eventual outcome.